Elements of Dystopian Fiction in the Modern Lithuanian Prose - Buividavičiūtė, Lina (Respectus Philologicus, 2015)
The theoretical problems and practical analysis of utopia and its subgenre dystopia are widely known in the global cultural discourse. Nevertheless, these analyses still remains almost terra incognita in the studies of Lithuanian prose. The aim of this article is to analyse and compare the ambivalent elements in these novels: Vilniaus pokeris (Vilnius Poker) by R. Gavelis, Užkeiktas miestas (The Town under the Spell) by R. Lankauskas, and Anapus rytojaus (Beyond Tomorrow) by J. Jankus. This article is based on the hermeneutical methodology and the context of existentialism. The theoretical part of the article “Dystopian World” describes the main sources, features, and polemical issues of genre. The first practical part “The Social-Historical Subordinated Dystopia in Lithuanian Literature” analyses the concrete historical and cultural features of the dystopian genre. The features of ontological-existential dystopia are described in the second practical part of the paper.
Keywords: utopia; dystopia; Lithuanian prose; novel; totalitarianism; history; society; existentialism; modernism; postmodernism